Pelvic actinomycosis three years after colporrhaphy: A case report - Stephen Davick; Samiksha Annira; Tyler Schwiesow (Elsevier, 2021)
A 57-year-old patient presented with vaginal discharge and was found to have a pelvic abscess with A. turicensis and Streptococcus constellatus, with likely nidus of infection being a non-absorbable suture placed during colporrhaphy three years prior. She was treated with drain placement and antibiotics. Post-hospitalization, her colporrhaphy suture was removed. Subsequently the drain output decreased and this was removed as well. She had a total course of 6 weeks of amoxicillin/clavulanate, with complete resolution of her abscess.